A5 region modulation of the cardiorespiratory responses evoked from parabrachial cell bodies in the anaesthetised rat - Dawid-Milner, Marc Stefan; Lara-Muñoz, José Pablo; López de Miguel, M Pilar; López-González, Manuel Víctor; Spyer, KM; González-Barón, Salvador (Elsevier, 2003)
We have examined the importance of the A5 region modulating cardiorespiratory responses evoked from the parabrachial complex (PB) in spontaneously breathing rats. Cardiorespiratory changes were analyzed in response to electrical stimulation and glutamate microinjections into the PB (10–20 nl, 1–2 nmol) before and after ipsilateral microinjection of muscimol (50 nl, 0.25 nmol) or lidocaine (50 nl, 0.5 nmol) within the A5 region. Stimulation of medial parabrachial and Ko¨lliker–Fuse nuclei (mPB-KF) evoked a decrease in respiratory rate (P,0.001) with a rise in blood pressure (P,0.001) and heart rate (P,0.05). After muscimol or lidocaine microinjections within the A5 region, the pressor and heart rate responses to mPB-KF stimulation were reduced (P,0.05, both cases). Muscimol within the A5 region altered the respiratory response to glutamate stimulation of mPB-KF, evoking an increase in respiratory rate (P,0.05). Lidocaine abolished the respiratory response to mPB-KF stimulation. Stimulation of the lateral parabrachial nuclei (lPB) caused an increase in respiratory rate (P,0.001) with a rise in blood pressure (P,0.001) and heart rate (P,0.05). Muscimol or lidocaine microinjections within A5 region decreased heart rate (P,0.05) and pressor responses (P,0.05) evoked from lPB. The increase of respiratory rate persisted unchanged. To confirm functional interactions between A5 and PB, extracellular recordings of putative A5 neurones were obtained during PB stimulation. Eighty-three A5 cells were recorded, 35 were activated from the mPB-KF (42%). The results indicate that neurones of the A5 region participate in the cardiorespiratory response evoked from the different regions of the PB complex. The possible mechanisms involved in these interactions are discussed
Keywords: Respiración - Regulación - Modelos animales; Corazón - Regulación - Modelos animales; Experimentación animal; Parabrachial complex; A5 Region; Respiratory Control; Cardiovascular Control; Rat